Numerical modelling and analysis for nonlinear stiffness of subgrade soil subject to 3-D vehicle-track interaction - Li, Zheng; Xu, Lei; Liu, Pengfei; Wang, Weidong; Zeng, Zhiping (Transportation Geotechnics, 2023)
In this paper, a subgrade model with nonlinear stiffness is established and integrated into a previously constructed 3-D vehicle-track-subgrade (VTS) dynamic model, in which the prediction and assessment of the vehicle-induced railroad vibrations are achieved with high accuracy and versatility. The system excitations are originated from the initial and time-dependent geometric irregularity of the system, which includes several internal excitations, namely conventional rail irregularity and the soil deformation-induced track irregularity. In the numerical analysis, the nonlinear behavior of the subgrade soil is revealed by considering shear modulus and traffic loads. The numerical experiment indicates that subgrade soil has a greater dynamic stiffness reduction if the vehicle enters the soil region with initial deformations. Besides, it is shown that the soil vibrations will be significantly amplified once the vehicle running speed is larger than the Rayleigh wave velocity of the subgrade soil.